2020
DOI: 10.1021/acscatal.0c02000
|View full text |Cite
|
Sign up to set email alerts
|

Supported Metal Pair-Site Catalysts

Abstract: Complexes with neighboring metal centers and their analogues on surfaces are drawing increasing attention as catalysts. These include molecular homogeneous catalysts incorporating various ligands; enzymes; and solids that include pairs of metal atoms mounted on supports.Catalysts in this broad class are active for numerous reactions and offer unexplored opportunities to address challenging reactions, such as oxidation of methane and oxidation of water in artificial photosynthesis. The subject of supported meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 134 publications
1
77
0
Order By: Relevance
“…For the foreseeable future, carbon-based fuels, such as natural gas, petroleum, and biomass, will continue to be a significant part of our energy infrastructure, and interfacially engineered heterogeneous catalytic materials relying on transition metal (TM) species will continue to play a critical role in meeting our daily energy needs. [1][2][3][4] It has been demonstrated that once supported or confined, TMs, their oxide, carbide and nitrides particles exhibit promising performance with high activity and selectivity in selective conversion of methane, [5][6][7][8] low-temperature CO conversion, 9,10 selective hydrogenation/dehydrogenation, [11][12][13][14] bio-oil conversion and upgrading, [15][16][17][18] and water-gas shift reaction 19,20 . Existing literature on heterogeneous catalytic materials primarily emphasize their outstanding performance and complexity in kinetics and reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For the foreseeable future, carbon-based fuels, such as natural gas, petroleum, and biomass, will continue to be a significant part of our energy infrastructure, and interfacially engineered heterogeneous catalytic materials relying on transition metal (TM) species will continue to play a critical role in meeting our daily energy needs. [1][2][3][4] It has been demonstrated that once supported or confined, TMs, their oxide, carbide and nitrides particles exhibit promising performance with high activity and selectivity in selective conversion of methane, [5][6][7][8] low-temperature CO conversion, 9,10 selective hydrogenation/dehydrogenation, [11][12][13][14] bio-oil conversion and upgrading, [15][16][17][18] and water-gas shift reaction 19,20 . Existing literature on heterogeneous catalytic materials primarily emphasize their outstanding performance and complexity in kinetics and reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Further work has been done to observe the formation of dimers. [ 60 ] Dimers which may have bond lengths not typically found in nanoparticles might be detected by EXAFS but this can be obscured through scattering paths with destructive interference or that have a weak signal due to long bond lengths. In addition, if the atoms are not directly bound but in close proximity due to the joint binding site or a bridging atom, it can be challenging to use EXAFS to detect the dimer.…”
Section: S/tem Imaging and Eds Analysis Of Sacsmentioning
confidence: 99%
“…And the formation of unsaturated sites offers opportunities to lower the reaction energy barrier by changing ligand environments around metal center. [ 120 ] Finally, apart from the interaction between metal atoms and supports, there is also a synergistic effect between metal atoms. The synergistic effect between metal atoms in DACs/SCCs can change the adsorption mode of the reactants and optimize the reaction pathway, thereby it can significantly improve the catalytic activity and selectivity.…”
Section: Bridging Remarks Between Sacs and Dacs/sccsmentioning
confidence: 99%